2017
DOI: 10.4172/2157-7609.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Sub-Chronic Oral Toxicity Study of Methanolic Extract of Caesalpinia volkensii (Harms)

Abstract: Medicinal plant Caesalpinia volkensii is used to treat Malaria, conjunctivitis, retinoblastoma, and eyelid swelling as well as gonorrhoea and bilharzia. Animal toxicity information on this plant is limited. This medicinal plant was collected in Embu County in Kenya to evaluate its Acute and sub-chronic toxicity using Wistar rats. The rats were orally administered with different doses of the plants extracts. They were weighed on first day and after every 7 days during treatment with the extract. Signs of toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…On the whole, there were no significant changes in the body weight of the test and control rats. This is similar to the observation by Musila et al (2017) [21].…”
Section: Effects Of Seed Extracts On Weight Of Ratssupporting
confidence: 93%
“…On the whole, there were no significant changes in the body weight of the test and control rats. This is similar to the observation by Musila et al (2017) [21].…”
Section: Effects Of Seed Extracts On Weight Of Ratssupporting
confidence: 93%
“…Medicinal plants (crude extract, pure compound or derivative) are an unlimited source for the discovery of new medicines. Most of the natural products used in traditional medicine have solid scientific evidence regarding their biological activities (Ochoa et al, 2014;Musila et al, 2017;Tang et al, 2017). However, little information or evidence is available on the possible toxicity of medicinal plants to the consumers (Tang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, little information or evidence is available on the possible toxicity of medicinal plants to the consumers (Tang et al, 2017). Regarding the discovery and development of drugs, the concerns of health authorities, the pharmaceutical industry and patients must be taken into consideration (Musila et al, 2017). The prompt access to safe and efficient medicines, as well as animal welfare, are of primary interest to the general public, patients, and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…54 One of the toxicological parameters used for the assessment of plant extracts safety is the Median Lethal Dose (LD50), which is the amount of a drug required to cause mortality in half of the test population. 4, 49,50 In this study, an acute toxicity study of methanol stem extract of T. microptera revealed that the extract is safe at an LD50 of 1386 mg/kg bodyweight with mortality of 3 animals at 1600 mg/kg body weight of the extract (Table 2). 4 and Etuk et al 57 reported LD50 of 5000 mg/kg and 2000 mg/kg bodyweight ethanol stem extract of T. microptera.…”
Section: Resultsmentioning
confidence: 67%